Locating Digital Constitutionalism in India and South Asia- Preliminary Enquiry - Kumar, Pawan (Kathmandu School of Law Review, 2025)
As India completes its 75th anniversary of being a republic in 2025, exploring and enquiring whether digital constitutionalism is required in today’s digital realm becomes necessary. Constitutionalism is an inner trait of our Constitution, and when we adopted and enacted it, it became the heart and soul of it. The author argues in this paper the need for digital constitutionalism for India as our Constitution, drafted in 1950 and has been amended more than 100 times ensured the protection of rights and liberties in the physical world; ensuring democracy; restraining governments despotism and has been hailed as among the best working Constitution by many scholars around the world; will it work the same way it was envisioned in the digital age. The constitution as a grund norm must be interpreted according to current societal standards and in the digital age, it becomes important we look for digital constitutionalism. As digital technologies advance, so do the challenges and threats to our fundamental rights. India has the largest written Constitution in the world, and the question to be asked whether current constitutionalism can protect the digital rights and well-being of citizens or not in the coming decades. This necessitates a new paradigm: digital constitutionalism. The anthology which the author intends to answer in this paper is virtual era poses more threats to fundamental rights and their violations; South Asian constitutions must embrace digital constitutionalism. There always is the need for Constitutionalism as the working of the Constitution, the way it adapts to future challenges would depend upon the thoughtful persistence of the people whose lives it regulates but what would happen when we are living in the digital world and do not embrace the very idea of it? Will the present constitutionalism work or does it need transformation? In this paper, the author looks for answers which support the idea of having digital constitutionalism for India which can ensure digital democracy not only in India but in South Asia as well and which can be a new constitutional moment.